m6A Methyltransferase METTL14-Mediated Upregulation of Cytidine Deaminase Promoting Gemcitabine Resistance in Pancreatic Cancer - Zhang, Congjun; Ou, Shuangyan; Zhou, Yuan; Liu, Pei; Zhang, Peiying; Li, Ziqian; Xu, Ruocai; Li, Yuqiang (Frontiers in Oncology, 2021)
Objective Pancreatic cancer is one of the most lethal human malignancies. Gemcitabine is widely used to treat pancreatic cancer, and the resistance to chemotherapy is the major difficulty in treating the disease. N6-methyladenosine (m6A) modification, which regulates RNA splicing, stability, translocation, and translation, plays critical roles in cancer physiological and pathological processes. METTL14, an m6A Lmethyltransferase, was found deregulated in multiple cancer types. However, its role in gemcitabine resistance in pancreatic cancer remains elusive. Methods The mRNA and protein level of m6A modification associated genes were assessed by QRT-PCR and western blotting. Then, gemcitabine‐resistant pancreatic cancer cells were established. The growth of pancreatic cancer cells were analyzed using CCK8 assay and colony formation assay. METTL14 was depleted by using shRNA. The binding of p65 on METTL14 promoter was assessed by chromatin immunoprecipitation (ChIP) assay. Protein level of deoxycytidine kinase (DCK) and cytidine deaminase (CDA) was evaluated by western blotting. In vivo experiments were conducted to further confirm the critical role of METTL14 in gemcitabine resistance. Results We found that gemcitabine treatment significantly increased the expression of m6A methyltransferase METTL14, and METTL14 was up-regulated in gemcitabine-resistance human pancreatic cancer cells. Suppression of METTL14 obviously increased the sensitivity of gemcitabine in resistant cells. Moreover, we identified that transcriptional factor p65 targeted the promoter region of METTL14 and up-regulated its expression, which then increased the expression of cytidine deaminase (CDA), an enzyme inactivates gemcitabine. Furthermore, in vivo experiment showed that depletion of METTL14 rescue the response of resistance cell to gemcitabine in a xenograft model. Conclusion Our study suggested that METTL14 is a potential target for chemotherapy resistance in pancreatic cancer.